A case of neonatal cytomegalovirus infection with severe thrombocytopenia that was successfully managed with empiric antiviral therapy. (2020) - Fujimori, Kentaro; Yamada, Masaki; Maekawa, Takanobu; Yotani, Nobuyuki; Tamura, Ei-ichiro; Imadome, Ken-ichi; Kubota, Mitsuru; Ishiguro, Akira
Abstract: Antiviral therapy against cytomegalovirus (CMV) infection is indicated for symptomatic infection in the fetus and premature neonates. In mature neonates, the benefit of antiviral therapy for severe CMV infection remains controversial. Additionally, when diagnosing symptomatic CMV disease occurring during the early neonatal period, it is difficult to differentiate between congenital and acquired infections. We herein report a neonatal case of CMV infection complicated with severe thrombocytopenia that was successfully managed with antiviral treatment. A 21-day-old male infant presented with low-grade fever and erythema on his extremities. During outpatient follow-up, he developed petechiae and thrombocytopenia (platelet count 17, 000/μL). Subsequent serological examination and molecular detection of CMV confirmed the diagnosis of CMV infection. In consideration of the severe thrombocytopenia, antiviral therapy with valganciclovir 32 mg/kg/day was initiated. The platelet counts increased with decreasing CMV loads. After excluding congenital CMV infection, we discontinued antiviral therapy without relapse of the disease. The present case suggests that neonatal cases of severe symptomatic CMV infection may require antiviral therapy while excluding the possibility of congenital infection.